Fundamentos técnicos del voleibol y entrenamiento físico de estudiantes de institución educativa secundaria N°60993, Belén Iquitos 2024 - Padilla Panaifo, Leslie Yasbeck (2025)
The research presented on this occasion has as its main objective to determine the effect of the application of the technical fundamentals of volleyball in the specific training of third grade students of the Secondary Educational Institution No. 60993, Belén district, Iquitos 2024. The research is oriented to a quantitative approach, experimental type with experimental group and control group, as well as to the quasi experimental design, in a student population of 142 students, of which 71 were participants in an experimental group and 71 were in the control group, to whom observation was applied as a technique, using an observation sheet as an instrument as part of the pre-test and post-test. After applying the data collection instruments, the information was analyzed using descriptive statistics, for the instruments before using for the experimental group 9.53 ± 2.873 standard deviation and the control group 9.67 ± 2.950 standard deviation, concluding that the experimental and control groups begin the experiment under equal conditions, a requirement for any experiment with a control group. In the after the instruments showed similar standard deviations between them, those of the experimental group 26.96 ± 6.467 standard deviation and the control group 22.58 ± 6.397 standard deviation. as an effect of the application of the technical fundamentals of volleyball and physical training. Concluding the research stating that the level of knowledge on the technical foundations of volleyball in the application of the before could be determined that had a basic level of knowledge, that is to say many of them, only knew empirically the basic actions that an athlete who practices volleyball should know, after applying the training the level of knowledge improved significantly since it could be observed students who perform a correct rotation, a set, a pass, an efficient block, among other actions that contributed to the development of the skills and abilities of the students. Finally, it is recommended to continue researching factors that contribute to improving sports practice.